2017
DOI: 10.2807/1560-7917.es.2017.22.18.30526
|View full text |Cite
|
Sign up to set email alerts
|

West Nile virus surveillance in Europe: moving towards an integrated animal-human-vector approach

Abstract: This article uses the experience of five European countries to review the integrated approaches (human, animal and vector) for surveillance and monitoring of West Nile virus (WNV) at national and European levels. The epidemiological situation of West Nile fever in Europe is heterogeneous. No model of surveillance and monitoring fits all, hence this article merely encourages countries to implement the integrated approach that meets their needs. Integration of surveillance and monitoring activities conducted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
87
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 25 publications
0
87
0
4
Order By: Relevance
“…As a consequence, regions with co‐circulation of WNV and TBEV are increasing in numbers and the differentiation of the two pathogens becomes more and more important. Especially veterinary hosts like horses are critical for the monitoring of virus circulation and they may serve as sentinels for surveillance, control, and risk management programs aiming the early identification of virus circulation before human cases occur (Gossner et al, ; Kolodziejek et al, ; López‐Ruiz et al, ; Rocheleau et al, ). In Austria, seroprevalences among asymptomatic horses of up to 28% have been reported for TBEV (Rushton et al, ), and the first equine WNV cases were confirmed in 2016 (Kolodziejek et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, regions with co‐circulation of WNV and TBEV are increasing in numbers and the differentiation of the two pathogens becomes more and more important. Especially veterinary hosts like horses are critical for the monitoring of virus circulation and they may serve as sentinels for surveillance, control, and risk management programs aiming the early identification of virus circulation before human cases occur (Gossner et al, ; Kolodziejek et al, ; López‐Ruiz et al, ; Rocheleau et al, ). In Austria, seroprevalences among asymptomatic horses of up to 28% have been reported for TBEV (Rushton et al, ), and the first equine WNV cases were confirmed in 2016 (Kolodziejek et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…West Nile virus (WNV, Flaviviridae , Flavivirus ) is broadly distributed in the world, being the aetiological agent of a zoonotic disease with high impact in human and animal health. Circulation of the virus has been regularly reported in wide areas of Europe since 1998 (Gossner et al, ). At least five genetic lineages have been identified, but only two of them (lineages 1 and 2) have shown high expansion and relevance for animal and human health.…”
Section: Introductionmentioning
confidence: 99%
“…At least five genetic lineages have been identified, but only two of them (lineages 1 and 2) have shown high expansion and relevance for animal and human health. In response to this emerging threat, many affected (or at risk) countries are implementing surveillance programs which rely, at least in part, on monitoring animal populations at risk of exposure, including wild bird reservoirs (Gossner et al, ; Lustig, Sofer, Bucris, & Mendelson, ). Identification of WNV circulation by viral RNA detection is not practical due to the difficulties to find positive samples as a result of the short period of viremia (usually 4–6 days) caused by infections (Komar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, West Nile virus (WNV), Usutu virus (USUV) and tick‐borne encephalitis virus (TBEV) have circulated endemically in European countries in the last decade, raising concerns regarding both public and animal health (Beck et al., ). Consequently, integrated human, veterinary and vector surveillance systems for flaviviruses have been implemented in several European countries (Gossner et al., ). WNV and USUV belong to the mosquito‐borne flavivirus group and are generally maintained in an enzootic life cycle involving ornithophilic mosquitoes (mostly genus Culex ) as competent vectors and wild birds as main reservoir hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, West Nile virus (WNV), Usutu virus (USUV) and tick-borne encephalitis virus (TBEV) have circulated endemically in European countries in the last decade, raising concerns regarding both public and animal health (Beck et al, 2013). Consequently, integrated human, veterinary and vector surveillance systems for flaviviruses have been implemented in several European countries (Gossner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%